Extensibility in ORDBMS databases : an exploration of the data cartridge mechanism in Oracle9i - Ndakunda, Tulimevava Kaunapawa (Rhodes University, Faculty of Science, Department of Computer Science)
To support current and emerging database applications, Object-Relational Database Management Systems (ORDBMS) provide mechanisms to extend the data storage capabilities and the functionality of the database with application-specific types and methods. Using these mechanisms, the database may contain user-defined data types, large objects (LOBs), external procedures, extensible indexing, query optimisation techniques and other features that are treated in the same way as built-in database features . The many extensibility options provided by the ORDBMS, however, raise several implementation challenges that are not always obvious. This thesis examines a few of the key challenges that arise when extending Oracle database with new functionality. To realise the potential of extensibility in Oracle, the thesis used the problem area of image retrieval as the main test domain. Current research efforts in image retrieval are lagging behind the required retrieval, but are continuously improving. As better retrieval techniques become available, it is important that they are integrated into the available database systems to facilitate improved retrieval. The thesis also reports on the practical experiences gained from integrating an extensible indexing scenario. Sample scenarios are integrated in Oracle9i database using the data cartridge mechanism, which allows Oracle database functionality to be extended with new functional components. The integration demonstrates how additional functionality may be effectively applied to both general and specialised domains in the database. It also reveals alternative design options that allow data cartridge developers, most of who are not database server experts, to extend the database. The thesis is concluded with some of the key observations and options that designers must consider when extending the database with new functionality. The main challenges for developers are the learning curve required to understand the data cartridge framework and the ability to adapt already developed code within the constraints of the data cartridge using the provided extensibility APls. Maximum reusability relies on making good choices for the basic functions, out of which specialised functions can be built.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Database management; Oracle (Computer file)